A Hybrid IDS Architecture Based on the Immune System - Reis, Marcelo; Paula, Fabrício; Fernandes, Diego; Geus, Paulo (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2002: Anais do II Workshop em Segurança de Sistemas Computacionais, 2002)
The human immune system provides a rich source of inspiration for computer network security. By exploring this analogy, the authors propose a hybrid intrusion detection architecture that has the same learning and adaptive capability of the human immune system.